Understanding the roles of images and intermodal relationships for optimized use of visual and verbal resources in Vietnam’s textbooks for lower secondary levels - Febrianti, Yusnita; Vu, Thao (citeus, 2023)
The study investigates the roles of images and intermodal relationships of both language and images in two English textbooks used in Vietnamese lower secondary schools, namely Tieng Anh and Solutions textbooks to gain insights on the ways to optimise the use of both language and images as resources in teaching and learning activities. Kress and Van Leeuwen’s (1996, 2006) framework on the grammar of visual design is used to analyse the images, looking at the types of image representations and the compositional meanings. The language-image relationships in the books, on the other hand, are analysed using the framework of Intermodal Identification (Unsworth & Cleirigh, 2014). Intermodal identification is built on the notion that language complements the meaning of the image and vice versa. Language identifies image by glossing the image participants which are not encoded in the language elements. Image identifies language in three aspects: intensive to visualise quality such as shape, colour, or texture, possessive to visualise additional participants which are not explicitly addressed in the language and circumstantial to visualise the elements of locations in the language. While image in textbooks has always been considered essential as a source of teaching and learning materials as well as helping students to learn, this study suggests that the role of image is augmented when juxtaposed with the accompanying language. The study implies the need for further investigation, for example in the classroom action research on how language and image resources can be utilised in teaching and learning activities. Also, the result of the study may be replicated to analyse language-image relationship in different samples of textbooks.